Pengaruh Viral Marketing, Brand Image dan Kepercayaan Pelanggan Terhadap Keputusan Pembelian Purbasari Melalui Aplikasi Tiktok di Kota Batam - Bellina Sihombing, Syintia; Erni Husein, Alice (DINASTI RESEARCH, 2025)
Rapid technological developments have a significant impact on business development. Increasingly tight competition requires companies to be able to compete in order to maintain their existence in the business world. The purpose of this study was to determine whether viral marketing, brand image, and customer trust affect purchasing decisions. This study was conducted in Batam City with the subject of Purbasari through the TikTok application with a total of 100 respondents. The type of research used is quantitative research with a survey data collection method by distributing questionnaires. The results of the study showed that viral marketing had a positive and significant effect on Purbasari's purchasing decisions through TikTok, brand image had a positive and significant effect on Purbasari's purchasing decisions through TikTok, and customer trust had a positive and significant effect on Purbasari's purchasing decisions through TikTok.